Pengaruh Gaya Hidup terhadap Keputusan Keuangan melalui Literasi Keuangan pada Mahasiswa Jurusan Manajemen FEB Unismuh Makassar - Aqidah Islamiah; Andi Arifwangsa Adiningrat; Sahrullah Sahrullah (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of lifestyle on financial decisions through financial literacy as a mediating variable among Management students at the Faculty of Economics and Business, Universitas Muhammadiyah Makassar. The research is motivated by the increasing influence of lifestyle trends and consumption patterns among university students, which may affect their ability to make sound financial decisions. This study employs a quantitative approach with an explanatory causal design to examine both direct and indirect relationships among the variables. The sample was selected using a purposive sampling technique and consisted of 100 student respondents who met predetermined criteria. Primary data were collected through structured questionnaires distributed to the participants. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results indicate that lifestyle has a positive and significant effect on financial literacy, and financial literacy has a positive and significant effect on financial decisions. Furthermore, financial literacy is proven to mediate the relationship between lifestyle and financial decisions. These findings suggest that financial literacy plays a crucial role in guiding students’ lifestyles toward more rational, responsible, and wise financial decision-making behavior.